Effect of pH on the Phase Equilibrium of a Ternary Mixture of Neopentyl Glycol, Salt, and Water - Y. Zhang; D. G. Li (Chemical and Biochemical Engineering Quarterly)
The ternary two-liquid phase system consisting of neopentyl glycol, sodium formate, and water was studied at pH values of 3, 4, 5, and 6. This study examined the effect of pH on phase diagrams, focusing on the length and slope of the tie-lines between the two conjugated phases. The results showed that the two-phase region expanded, and both the length and slope of the tie-lines increased with rising pH values. The phase behavior was analyzed using the Bancroft, Othmer-Tobias, and Hand equations, the measured data showing acceptable consistency, and the Bancroft equation providing the best fit. The plait points at different pH values were estimated through extrapolation, and empirical equations were used to fit the data and gave good results. The fitted curves matched the data well.